COMPARATIVE STUDY: FAMILY SUPPORT FOR STROKE PATIENTS BASED ON DEMOGRAPHIC PROFILE, TYPE OF STROKE, AND DURATION OF HOSPITALIZATION - Anderson, Elisa (Fakultas Keperawatan, Universitas Klabat, 2025)
Family support is a crucial component in the care process for stroke patients, but there is still little research evaluating its intensity based on demographic profiles and clinical conditions. This study aims to analyze the relationship between demographic profiles (age, gender, education level, occupation, income), stroke type, and length of hospital stay on family support for stroke patients. This study used an analytical cross-sectional method with a cross-sectional approach involving 62 stroke patients treated at a hospital in Manado. Data was collected through survey sheets and observations combined with family support questionnaires. The data were analyzed using the Mann–Whitney and Kruskal–Wallis tests. The results showed that the highest level of family support was found in young-old patients (60–74 years), those with higher education, those with income above the minimum wage, and those with a long hospitalization duration (≥8 days). Meanwhile, in the correlation test, gender, occupation, and type of stroke did not show significant differences in family support (p>.05). However, age, education, family income, and length of hospital stay showed significant differences in the intensity of family support (p<.05) when providing assistance to stroke patients who were hospitalize. Recommendations that can be given in this study are the design of family education programs based on patient demographic profiles, such as health literacy modules for low-educated families and coping skills training for low-income families, as well as implementing family-centered care that involves family members from the first day of hospitalization. Dukungan keluarga merupakan komponen krusial dalam proses perawatan pasien stroke, namun masih sedikit penelitian yang mengevaluasi intensitasnya berdasarkan profil demografi dan kondisi klinisnya. Studi ini bertujuan untuk menganalisis hubungan antara profil demografi (usia, jenis kelamin, tingkat pendidikan, pekerjaan, pendapatan), jenis stroke, dan durasi rawat inap terhadap dukungan keluarga pada pasien stroke. Studi ini menggunakan metode analytical cross-sectional study yang melibatkan 62 pasien stroke yang dirawat di salah satu rumah sakit di Manado. Data dikumpulkan melalui lembar survei dan observasi yang dikombinasikan dengan kuesioner dukungan keluarga. Data yang tersebut dianalisis menggunakan uji deskriptif, Mann–Whitney, dan Kruskal–Wallis. Temuan hasil menunjukkan bahwa dukungan keluarga tertinggi ditemukan pada pasien usia young-old (60–74 tahun), berpendidikan tinggi, berpendapatan di atas upah minimun, dan durasi rawat inap panjang (≥8 hari). Sementara pada uji hubungan, jenis kelamin, pekerjaan, dan tipe stroke tidak menunjukkan perbedaan dukungan keluarga yang signifikan (P>,005). Sedangkan untuk faktor usia, pendidikan, pendapatan keluarga, dan lama rawat inap mempunyai perbedaan intensitas dukungan keluarga yang signifikan (P<,005) saat memberikan pendampingan pada pasien stroke yang sedang dirawat inap. Rekomendasi yang dapat diberikan dalam studi ini adalah perancangan program edukasi keluarga berdasarkan profil demografi pasien, seperti modul literasi kesehatan bagi keluarga berpendidikan rendah dan pelatihan coping skills untuk keluarga berpendapatan terbatas, serta menerapkan family centered care yang melibatkan anggota keluarga sejak hari pertama rawat inap.